Gender differences in transcriptional signature of developing rat testes and ovaries following embryonic exposure to 2,3,7,8-TCDD. - Solange Magre; Diane Rebourcet; Muhammad Ishaq; Richard Wargnier; Cyrille Debard; Emmanuelle Meugnier; Hubert Vidal; Joëlle Cohen-Tannoudji; Brigitte Le Magueresse-Battistoni (PLoS ONE, 2012)
Dioxins are persistent organic pollutants interfering with endocrine systems and causing reproductive and developmental disorders. The objective of our project was to determine the impact of an in utero exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on reproductive function of male and female offspring in the rat with a special emphasis on the immature period. We used a low dose of TCDD (unique exposure by oral gavage of 200 ng/kg at 15.5 days of gestation) in order to mirror a response to an environmental dose of TCDD not altering fertility of the progeny. We choose a global gene expression approach using Affymetrix microarray analysis, and testes of 5 days and ovaries of 14 days of age. Less than 1% of the expressed genes in gonads were altered following embryonic TCDD exposure; specifically, 113 genes in ovaries and 56 in testes with 7 genes common to both sex gonads. It included the repressor of the aryl hydrocarbon receptor (Ahrr), the chemokines Ccl5 and Cxcl4 previously shown to be regulated by dioxin in testis, Pgds2/Hpgds and 3 others uncharacterized. To validate and extend the microarray data we realized real-time PCR on gonads at various developmental periods of interest (from 3 to 25 days for ovaries, from 5 to the adult age for testes). Overall, our results evidenced that both sex gonads responded differently to TCDD exposure. For example, we observed induction of the canonic battery of TCDD-induced genes coding enzymes of the detoxifying machinery in ovaries aged of 3-14 days of age (except Cyp1a1 induced at 3-10 days) but not in testes of 5 days (except Ahrr). We also illustrated that inflammatory pathway is one pathway activated by TCDD in gonads. Finally, we identified several new genes targeted by TCDD including Fgf13 in testis and one gene, Ptgds2/Hpgds regulated in the two sex gonads.